Hürthle Cells on Fine-Needle Aspiration Cytology Are Important for Risk Assessment of Focally PET/CT FDG Avid Thyroid Nodules - Poller, David N. (Cancers (Basel), 2020)
SIMPLE SUMMARY: PET/CT fluorodeoxyglucose (FDG) scans are routinely used in patients to detect signs of malignant tumours or evidence of inflammation in the body. A total of 1–2% of patients show focal thyroid gland FDG uptake and 35–40% are malignant. FDG also detects metabolically active lesions containing mitochondria, known as Hürthle cells. Over 3 years, 47 patients in one hospital were found to have focal thyroid gland uptake. A total of 18 (38.2%) of the patients had malignancy, 15 (31.9%) had benign lesions that contained Hürthle cells and 14 (29.8%) had focally increased thyroid gland FDG PET/CT uptake with no cause identified. Exclusion of the Hürthle cell patients increased the risk of malignancy of the remaining PET-positive nodules from 38% to 68%. It is important to recognize Hürthle cells on FNA cytology in FDG PET/CT-positive nodules as this affects the risk of malignancy and the clinical management of focally FDG PET/CT-positive nodules. ABSTRACT: This study assesses the role of [(18)F] FDG PET/CT, fine needle aspiration (FNA) cytology and ultrasound in the 1–2% of patients with focally positive thyroid nodules on FDG PET/CT. All FDG PET/CT scans with focally increased thyroid FDG PET/CT uptake performed over 37 months in one institution were matched to patients undergoing thyroid FNA. Diffuse FDG PET/CT uptake patients were excluded. A total of 47 patients showed focally increased thyroid uptake. Consistent with previous studies, 18 (38.2%) patients had malignancy—12 primary thyroid carcinoma, 1 parathyroid carcinoma, 3 metastatic carcinoma to the thyroid and 2 lymphoma. A total of 15 (31.9%) lesions categorized as non-malignant contained Hürthle cells/oncocytes. A total of 14 lesions (29.8%) had focally increased FDG PET/CT uptake with no specific cytological or histopathological cause identified. No focally PET avid Hürthle cell/oncocytic lesions were found to be malignant. Exclusion of oncocytic lesions increased the calculated risk of malignancy (ROM) of focally PET avid nodules from 38% to 68%. It may be useful to exclude focally FDG PET/CT avid Hürthle cell/oncocytic lesions, typically reported as follicular neoplasm or suspicious for a follicular neoplasm, Hürthle cell type (Oncocytic) type, RCPath Thy 3F: Bethesda IV or sometimes Thy 3a: Bethesda III FNAs) from ROM calculations. Oncocytic focally PET/CT FDG avid lesions appear of comparatively lower risk of malignancy and require investigation or operation but these lesions should be readily identified by FNA cytology on diagnostic work up of focally PET avid thyroid nodules.